Multinational Enterprises from Emerging Economies : Seeking New Theoretical Framework - Klimek, Artur (Korporacje transnarodowe z krajów wschodzących : poszukiwanie nowych podstaw teoretycznych, 2010)
The multinational enterprises (MNEs) from emerging economies have become important international players due to a few reasons. First of all, their activities have affected the level of development of their home economies, but also influenced host economies. So called "new multinationals" have also challenged well established companies from developed countries and forced them to redesign their operations. The aim of the paper is an attempt to develop unified theoretical foundations for expansion of MNEs from emerging countries. The analysis will predominantly focus on enterprises from India and China, but in order to present complete overview, the author will also take into consideration MNEs from Latin America and Central and Eastern Europe.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 134, s. 46-55
Keywords: multinational companies; foreign direct investment; emerging economies